Effect of Dietary Supplementation of Garlic (Allium sativum) and Black Pepper (Piper nigrum L.) Powder on Growth Performance of Broilers in Konkan Region of India - Bharambe, V. Y.; Shinde, S. S.; Garde, Y. D. (Indian Journal of Hill Farming, 2018)
An experiment was conducted to assess the effect of dietary supplementation of garlic (Allium sativum) bulb and black pepper (Piper nigrum L.) powder as herbal feed additives on feed intake, growth performance in broilers; A total of 320 day old broilers chicks of Vencobb-400 strain were divided into four treatment groups with four replicates of 20 chicks in each treatment using completely randomized design. The control group (C) was fed on basal diet without any supplementation and other three treatment groups were supplementation with 0.5% garlic bulb powder 0.5% black pepper powder and 0.5% of each supplement (garlic bulb powder and black pepper powder) in G, B and GB groups, respectively statistical analysis of data revealed no effect of garlic and black pepper alone or no in combination of feed intake of experimental birds. Growth performance and efficiency of feed utilization for growth was significantly (P<0.05) higher in the garlic supplemented group (G and GB) as compared to C and B groups. The study reveals that supplementation of garlic bulb alone or in combination with black pepper seed powder improves growth performance and feed utilization efficiency in intensive broiler production in agro-ecological conditions of Konkan in India.